Affective valence facilitates spatial detection on vertical axis: shorter time strengthens effect - Xie, Jiushu; Huang, Yanli; Wang, Ruiming; Liu, Wenjuan (Frontiers in Psychology, 2015)
Affective concepts can be described in terms of space, which is known as the valence-space metaphor. Previous studies have not investigated either the specifics of this metaphor on the transverse and vertical axes or the time course of this metaphoric association. With Chinese participants, we used a spatial cue task to study the valence-space metaphor on the transverse (left-and-right; Experiment 1A) and vertical (upper-and-lower; Experiment 1B) axes. After being shown an affective word and asked to keep it in mind, the participants were given a spatial target detection task. The results revealed that the metaphoric association was only found on the vertical axis. More specifically, keeping a positive word in mind facilitated the detection of the upper target, but no such effect was found in the detection of the lower target. Furthermore, in Experiment 2, we manipulated the duration of time (100, 500, and 1000 ms) between the offset of the affective word and the onset of the spatial target (i.e., interstimulus intervals, ISI), to test the dynamic time course of the valence-space metaphor on the vertical axis. The results showed that when ISI was 100 ms, keeping a positive word in mind facilitated the detection of the upper target and keeping a negative word in mind facilitated the detection of the lower target. However, when the ISI was 500 or 1000 ms, keeping a positive word in mind facilitated the detection of the upper target and no such effect was found in the detection of the lower target, indicating that ISI might be important in the valence-space metaphoric association. In sum, we found that the processing of affective valence activated the vertical spatial axis but not the transverse axis. Further, the association might be modulated by ISI, indicating that it may be related to attention allocation.